Renal function and the effects of vericiguat in patients with worsening heart failure with reduced ejection fraction: insights from the VICTORIA (Vericiguat Global Study in Subjects with HFrEF) trial - Voors, Adriaan A.; Mulder, Hillary; Reyes, Eugene; Cowie, Martin R.; Lassus, Johan; Hernandez, Adrian F.; Ezekowitz, Justin A.; Butler, Javed; O'Connor, Christopher M.; Koglin, Joerg; Lam, Carolyn S.P.; Pieske, Burkert; et al. (European journal of heart failure, 2021)
Aims Vericiguat reduced the primary composite outcome of cardiovascular death or heart failure (HF) hospitalization in patients with worsening HF with reduced ejection fraction (HFrEF) and a lower limit of baseline estimated glomerular filtration rate (eGFR) of 15 mL/min/1.73 m2. We evaluated the relationship between the efficacy of vericiguat and baseline and subsequent changes in renal function. Methods and results In VICTORIA, core laboratory serum creatinine was measured at baseline (n = 4956) and weeks 16, 32, and 48. Worsening renal function (WRF), defined as an increase ≥0.3 mg/dL in creatinine from baseline to week 16, was assessed via a Cox model with respect to subsequent primary events. Mean age was 69 years, 24% were female, and mean baseline eGFR was 61 mL/min/1.73 m2. During 48 weeks of treatment, the trajectories in eGFR and creatinine with vericiguat were similar to placebo (P = 0.50 and 0.18). The beneficial effects of vericiguat on the primary outcome were not influenced by baseline eGFR (interaction P = 0.48). WRF occurred in 15% of patients and was associated with worse outcomes (adjusted hazard ratio 1.28, 95% confidence interval 1.11–1.47; P < 0.001), but the beneficial effects of vericiguat on the primary outcome were similar in patients with or without WRF (interaction P = 0.76). Conclusion Renal function trajectories were similar between vericiguat‐ and placebo‐treated patients and the beneficial effects of vericiguat on the primary outcome were consistent across the full range of eGFR and irrespective of WRF. The left panel shows no differences in the change in creatinine (P = 0.18) between the vericiguat and placebo groups, as evaluated by the interaction between treatment and study visit in the model. The right panel shows a natural cubic spline plot showing that the treatment effect of vericiguat on the primary outcome was similar across the full range of estimated glomerular filtration rate (eGFR) (P = 0.23).